Studies on soil quality indices and agricultural functionality potentials of Ariara Market Solid Waste Dumpsite Aba, Abia State, Nigeria - Chinyere, G. C.; K. U. Osuocha, O. R. Chima Ezika (Journal of Scientific Agriculture, 2017)
Soil physicochemical properties and selected enzyme activities were assessed at thirteen different points at a depth of 0-45cm (sample A) and 46-90cm (sample B) from Ariara Market solid waste dump site Aba, Abia State. Control samples were collected 100m away from discharge point devoid of solid waste impaction. The studied points were discharge point (DC), 4 meters away East (E1), West (W1), North (N1), and South (S1) from the center of the dumpsite and 8 meters away East (E2), West (W2), North (N2) and South (S2) from the center of the dumpsite. Results indicated an alkaline pH for all the studied points. Significantly high (p<0.05) temperatures and percentage moisture contents were also obtained at the discharge points (DC) of the dumpsite compared to control points. Similarly, dumpsite alkaline phosphatase, hydrogen peroxidase, dehydrogenase and urease activities were significantly (p<0.05) higher than those of control points at 0-45cm depth (sample A). These finding suggest that wastes from this dumpsite could be harnessed as biofertilizers for agricultural purposes.